2007
DOI: 10.1590/s1516-635x2007000400001
|View full text |Cite
|
Sign up to set email alerts
|

Correlations among behavior, performance and environment in broiler breeders using multivariate analysis

Abstract: Animal welfare issues have received much attention not only to supply farmed animal requirements, but also to ethical and cultural public concerns. Daily collected information, as well as the systematic follow-up of production stages, produces important statistical data for production assessment and control, as well as for improvement possibilities. In this scenario, this research study analyzed behavioral, production, and environmental data using Main Component Multivariable Analysis, which correlated observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 7 publications
0
6
0
2
Order By: Relevance
“…This may explain the fact that this behavior was more frequent at the hottest times of the day, between 13.00 and 17.00 h, whereas at 9:00 h, its frequency was lower than 3.0%. Pereira et al (2007) reported that the frequency of dust bathing is positively correlated with temperature. According to the European Commission (2000), this is considered important for birds because it helps maintain plumage in good condition.…”
Section: Resultsmentioning
confidence: 99%
“…This may explain the fact that this behavior was more frequent at the hottest times of the day, between 13.00 and 17.00 h, whereas at 9:00 h, its frequency was lower than 3.0%. Pereira et al (2007) reported that the frequency of dust bathing is positively correlated with temperature. According to the European Commission (2000), this is considered important for birds because it helps maintain plumage in good condition.…”
Section: Resultsmentioning
confidence: 99%
“…Após os dez primeiros dias de idade das aves, os ventiladores foram acionados, nos períodos mais quentes do dia, com a finalidade de diminuir o estresse calórico. A construção do etograma que é o inventário dos padrões de comportamento observados nos animais (Tabela 3) foi adaptada, segundo metodologia descrita por Salgado et al (2007), Bizeray et al (2002, Estevez et al (2003). As observações comportamentais foram realizadas visualmente por pessoas que passaram por treinamentos prévios nos boxes e com as aves identificadas, equipadas com pranchetas e lápis, sendo uma pessoa para acompanhar três boxes.…”
Section: Methodsunclassified
“…A moderate thermal environment was reported throughout the poultry house with tunnel-like ventilation and pad cooling. These factors contributed towards an increase in production, improvement in egg quality and decrease in laying hens mortality rates, as envisaged by assay by Faria et al (2001), Barbosa Filho et al (2006, Pereira et al (2007) and Trindade et al (2007). High performance of the poultry house with tunnel-like ventilation system (negative pressure) has also been registered by Abreu and Abreu (2011) in so far as the poultry house was totally sealed and adequately climatized.…”
Section: Economic Viability Of Climatization Systemsmentioning
confidence: 99%